High-performance flexible supercapatteries enabled by binder-free two-dimensional mesoporous ultrathin nickel-ferrite nanosheets. (22nd March 2021) - Xi, Jianguo; Javed, Muhammad Sufyan; Asim, Sumreen; Idrees, Muhammad; Shah, Syed Shoaib Ahmad; Assiri, Mohammad A.; Mai, Wenjie; Hu, Chenguo
Abstract : To accomplish the efficient and high-performance supercapattery, electrochemically active materials with multi-component and rational morphological architectures are proposed. Abstract : To accomplish an efficient and high-performance flexible supercapattery, electrochemically active materials with multicomponent and rational morphological architectures are highly enviable. Herein, we demonstrate dual-morphology-based mesoporous nickel-ferrite nanoparticles embedded in ultra-thin nanosheets (NiFe2 O4 -NP-NS) grown directly on a carbon cloth (CC) substrate to develop a free-standing electrode (NiFe2 O4 -NP-NS@CC) for a flexible supercapattery. Owing to the symmetric effects of bimetallic oxides, porosity with a higher surface area and dual morphological impact, the designed electrode conferred significantly enhanced electrochemical performance in aqueous as well as solid-state electrolytes. The binder-free architecture offered an excellent capacity of 965 C g -1 (1608 F g −1 ) at 5 mV s −1 with high coulombic efficiency and a good capacity retention of 94.20% over 5000 cycles, while the single morphology–based electrode showed only 551 C g −1 (919 F g −1 ) at 5 mV s −1 with a capacity retention of 90.50% over 5000 cycles under identical conditions. A redox-reaction mechanism is proposed based on ex situ XRD, XPS, and TEM analysis, and it further quantitatively distinguished the pseudocapacitive and diffusion-controlled charge storage proportions of NiFe2 O4 -NP-NS@CC cathodes in aqueous electrolytes. Additionally, the flexible supercapattery (NiFe2 O4 -NP-NS@CC//NPC) exhibits an outstanding energy density of 69 W h kg −1 at a power density of 771 W kg −1 with highly flexible features, which exceeds that of supercapacitors. These results present the fabricated device as a promising candidate in the field of energy storage.